Peningkatan Kapasitas Masyarakat dalam Pengendalian Hipertensi: Program Edukasi dan Intervensi Kesehatan - Yudanari, Yunita Galih; Putri Dewi Siti Aisyah; Ahmad Ali Rohman (UNIVERSITAS NGUDI WALUYO, 2024)
Hypertension is one of the most common health issues encountered in society and can affect all age groups, from teenagers to the elderly. The community service activity titled